Some experiences on the planning and implementation of soil and water conservation measures in a 4-HA corn-based farm in Kay-anlog, Calamba City initial results - Villano, Manolo G. (Philippine agricultural mechanization journal)
A 4-ha corn-based diversified farm of rolling terrain in Kay-anlog, Calamba City has been experiencing low crop yield level attributed in part to high soil erosion rate. To avert further decrease in crop yield and help the farmer gain higher production in the long term, a soil and water conservation plan for the farm has been formulated and currently being implemented. Basic data generated includes soil properties, climate and topographic map. Using a modified universal soil loss equation (MUSCLE), the erosion rate under current farming practices is about 28 tons/ha per year. Based mainly on land slopes, the recommended conservation measures are construction of channel or graded broad-base terraces and bench terraces on areas with slopes from 0 to 12 percent and 12 to 27 percent, respectively. In addition, two storm water drainage canals were recommended to intercept runoff from upstream areas and from the terraces and dispose them to outlets outside the farm. After implementation, the estimated average erosion rate by the MUSLE will be reduced to about 5 tons/ha per year which is acceptable for the area. To date, two bench terraces and a storm water drain have been completed. Even with these initial structures, the farmer was convinced that indeed soil erosion rate may have been decreased. It is then recommended that the planned resources be fully implemented to convince other farmers in practicing conservation farming.